ASSESSMENT OF NATURAL IONIZING RADIATION IN TWO TERTIARY INSTITUTIONS OF NIGER STATE - Usman, Yusuf Tanko; Jibrin, A. Y.; Ishaq, Y.; Bello, S.; Yahaya, M. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Background ionizing radiation attributed to natural sources has over the years been at increase due to increase in infrastructural facilities and population inducing more human activities within campuses. This called for very great concern because of it effects on the human at higher exposure doses. Consequently, the Assessment of the Natural Ionizing Radiation was carried out at Ibrahim Badamasi Babangida University, Lapai (IBBUL) and Niger State Polytechnic, Zungeru (NSPZ) with approximate populations of 7000 and 5200 students respectively. A portable Geiger-Mueller dosimeter was used at 19 different locations within the two tertiary institutions. The results revealed the Dose Rate variation from 0.14 to 0.186 Î¼Svâ„hr, at IBBUL, while at NSPZ the variation was from 0.12 to 0.158 Î¼Svâ„hr. For all the locations the mean Dose Rate was 0.154 Î¼Svâ„hr with a standard deviation of 0.0195 Î¼Svâ„hr. Generally, average Annual Effective Dose Rate obtained is 0.27 mSv/annum which fell within the recommended alarming limit of 1 mSv/annum given by the International Commission on Radiation Protection (ICRP) for non-occupational population exposure. This implied no adverse impact on the tenements within the two tertiary Institutions. However, part of the recommendations is that more work needs to be done on the soil to characterize the areas for possible radioactive source deposits which may be up to alarming magnitude in the near future.
Keywords: Background Gamma Radiation, Dose Rate, Annual Effective Dose, radioactive deposits, artesian miners